(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
In modern conditions, financial innovation is key to the efficient functioning of the financial market and the transition to a digital economy. Digital technologies will transform the methods of work of state bodies, enterprises, individual entrepreneurs and citizens, facilitating the fulfillment of their tasks. Digital innovations stimulate the development of the digital economy and society, enable the use of developments in many areas and lead to a transformation of the economy. Companies with a high level of organizational and human capital will be most likely to benefit from digital technology investments. These companies are quite flexible and capable of maximizing the benefits of their investments by identifying and exploiting opportunities for sales growth, process reorganization and improved production efficiency. The article highlights new vectors that promote the development of modern technologies in the financial market, as well as problems of its innovative development in the conditions of digital transformation of business. An important condition for the emergence of financial innovation is the set of factors of external influence. First, they include the results of processes of globalization and international integration, increased competition in financial markets, global consolidation, rapid growth of information technology and a number of others. Globalization, because of deregulation processes and easing restrictions on access to regional financial markets, has significantly increased the profitability of activities by accelerating the free movement of capital and the widespread use of new instruments, which in turn required new ways and approaches to risk management. In addition, globalization encourages competition among financial intermediaries who seek to capture certain market segments on an international scale. The interplay of competition and innovation has a stimulating character. Competition forces financial companies to develop new products and services and implement non-standard approaches to doing business. In turn, innovations open new lines of competition.